Impact of Information Society Research in the Global South - Chib, Arul; May, Julian; Barrantes, Roxana (Springer Nature Singapore : Imprint: Springer, 2015)
The second volume in the SIRCA book series investigates the impact of information society initiatives by extending the boundaries of academic research into the realm of practice. Global in scope, it includes contributions and research projects from Asia, Africa and Latin America. The international scholarly community has taken a variety of approaches to question the impact of information society initiatives on populations in the Global South. This book addresses two aspects- Impact of research: How is the research on ICTs in the Global South playing a role in creating an information society? (e.g. policy formulation, media coverage, implementation in practice) and Research on impact: What is the evidence for the impact of ICTs on society? (i.e. the objectives of socio-economic development). This volume brings together a multiplicity of voices and approaches from social scientific research to produce an engaging volume for a variety of stakeholders including academics, researchers, practitioners, policy-makers and those in the business and civil sectors of society.